Pseudogap e energia cinética de supercondutores não convencionais descritos por um modelo de Hubbard em duas dimensões - Motta, Giordano Paulo da (2020)
In conventional superconductors described by the Bardeen-Cooper-Schrieffer (BCS) Theory, the transition from the normal to the superconducting state is accompanied by a reduction in the potential energy and an increase in the kinetic energy. On the other hand, in high-temperature superconductors the potential and the kinetic energies present an unconventional behavior that may be strongly related to the pseudogap phenomena. In this work, the kinetic and potential energies in the superconducting state of the two-dimensional Hubbard model were analyzed. The model is investigated using the Green’s function method within a n-pole approximation, which allows superconductivity with dx2y2-wave pairing. In the present scenario, a pseudogap emerges near the anti-nodal points in the Fermi surface, when the strong coupling regime is reached. The results show that in the low doping region, the system enters the strong coupling regime and the opening of a pseudogap is followed by a decrease in the kinetic energy and an increase in the potential energy. A phase diagram of Coulomb interaction U versus the occupation nT is also presented. This phase diagram shows clearly that the pseudogap regime coincides with the strong coupling regime in which the kinetic and potential energies present an unconventional behavior. The analysis of the density of states and the chemical potential showed that the unconventional behavior of the potential and kinetic energies occurs due to the pseudogap emergence in the high occupancy region. It was also observed that the pseudogap emergence, when the occupancy increases, is preceded by a change in the Fermi surface topology, which characterizes a Lifshitz transition. Both the pseudogap and the Lifshitz transition are affected by the next-nearest neighbor hopping t2 (of the Hubbard model). This result is in accordance with recent theoretical and experimental results for the Hubbard model and the cuprates.